2021
DOI: 10.1016/j.cub.2021.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing habenular activity is driven by forebrain networks and modulated by olfactory stimuli

Abstract: Summary Ongoing neural activity, which represents internal brain states, is constantly modulated by the sensory information that is generated by the environment. In this study, we show that the habenular circuits act as a major brain hub integrating the structured ongoing activity of the limbic forebrain circuitry and the olfactory information. We demonstrate that ancestral homologs of amygdala and hippocampus in zebrafish forebrain are the major drivers of ongoing habenular activity. We also reveal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 110 publications
(312 reference statements)
2
22
0
Order By: Relevance
“…Our results indicate differentiation of neurons in the olfactory bulb first, while areas of the pallium and subpallium show considerable expansion after 5dpf suggesting late maturation of these regions. This is in agreement with behavioural studies, which have shown that complex behaviours appear from 2 to 6 weeks post-fertilization (Valente et al, 2012; Aoki et al, 2013; Cheng et al, 2014; Dreosti et al, 2015; Lal et al, 2018; Stednitz et al, 2018; Tunbak et al, 2020; Bartoszek et al, 2021). As a consequence, most functional studies likely involving the role of the telencephalon, such as fear conditioning, social interaction, learning and memory, performed on older zebrafish.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicate differentiation of neurons in the olfactory bulb first, while areas of the pallium and subpallium show considerable expansion after 5dpf suggesting late maturation of these regions. This is in agreement with behavioural studies, which have shown that complex behaviours appear from 2 to 6 weeks post-fertilization (Valente et al, 2012; Aoki et al, 2013; Cheng et al, 2014; Dreosti et al, 2015; Lal et al, 2018; Stednitz et al, 2018; Tunbak et al, 2020; Bartoszek et al, 2021). As a consequence, most functional studies likely involving the role of the telencephalon, such as fear conditioning, social interaction, learning and memory, performed on older zebrafish.…”
Section: Discussionsupporting
confidence: 92%
“…Although the selective origin from or terminal projection sites within the habenula nuclei remains uncharacterized in fish, neural tracer studies in fish have revealed afferent connectivity of the habenula with some nodes of the fish SDMN such as the Vv (the teleostean homolog of the LS), Vd (the homolog of mammalian striatum), and POA ( Villani et al, 1996 ; Yañez and Anadón, 1996 ; Turner et al, 2016 ; Figure 1B ). A recent functional study demonstrated that microstimulation of the Dl and Dm (the homolog of mammalian hippocampus and BLA) elicit significant activation in the habenula neurons in juvenile zebrafish ( Bartoszek et al, 2021 ). Further, ongoing neural activities in the dHb are significantly correlated with the neural activities in the Dm and olfactory bulb, while vHb activity correlates more with the activity in the Dl rather than those in the Dm ( Bartoszek et al, 2021 ).…”
Section: Possible Connection Between the Habenula And The Social Deci...mentioning
confidence: 99%
“…A recent functional study demonstrated that microstimulation of the Dl and Dm (the homolog of mammalian hippocampus and BLA) elicit significant activation in the habenula neurons in juvenile zebrafish ( Bartoszek et al, 2021 ). Further, ongoing neural activities in the dHb are significantly correlated with the neural activities in the Dm and olfactory bulb, while vHb activity correlates more with the activity in the Dl rather than those in the Dm ( Bartoszek et al, 2021 ). Although no direct anatomical projections from the Dl or the Dm have been identified to innervate the habenula in fish, the primary afferents of the vHb originates from the ventral entopeduncular nucleus (vENT = teleostean basal ganglia) in zebrafish ( Amo et al, 2014 ; Turner et al, 2016 ).…”
Section: Possible Connection Between the Habenula And The Social Deci...mentioning
confidence: 99%
“…However, a study on zebrafish could not find similar connectivity (Yáñez et al, 2017 ). In juvenile and adult zebrafish, calcium imaging studies show that Dm is activated in response to odors (Diaz-Verdugo et al, 2019 ; Bartoszek et al, 2021 ). Thus, the teleost Dm receives sensory input similar to the mammalian BLA.…”
Section: Conserved Neural Connectivity Between Zebrafish and Mammalia...mentioning
confidence: 99%